Study on the Dynamic Performance of Armored Vehicle in Lateral Direction due to Firing Impact (Advances in Military Technology, 2016)
The purpose of this study is to analyze the performance of a 10 DOF wheeled armored vehicle in reponse to external disturbance due to firing recoil force, in lateral direction. An armored vehicle model was developed which consisted of 7 DOF handling model, weight distribution model, Pacejka tire model, 2 DOF Pitman Arm steering model and single DOF of gun model. A yaw moment occurred at the Center of Gravity (CG) of the armored vehicle caused by the impulse force generated during gun turret firing. This firing recoil force tends to create instability conditions for the armored vehicle during firing condition and affects the travelling path of the armored vehicle. The armored vehicle is evaluated using firing angle of 45° and 90°, caliber size of 57 and 75mm and two different speeds which are 40 and 60 km/h in order to analyze the dynamic performance of armored vehicle during firing. The armored vehicle is evaluated in terms of yaw rate, yaw angle, body sideslip angle, lateral acceleration and lateral displacement.
Keywords: Armoured vehicle; firing recoil force; firing angle; lateral motion; yaw motion